Are We Innovative? Increasing Perceptions of Nonprofit Innovation Through Leadership, Inclusion, and Commitment. (March 2021) - Brimhall, Kim C.
Innovation is particularly important for the sustainability, functioning, and improvement of public and nonprofit organizations. Researchers have called for the examination of how leaders can foster innovation in the nonprofit context. This study examined whether climate for inclusion and affective commitment were key mechanisms by which transformational leadership increased perceptions of innovation in a diverse nonprofit health care organization. Data were collected at three points in 6-month intervals from a U.S. nonprofit hospital. Longitudinal multilevel path analysis revealed transformational leaders increase perceptions of nonprofit innovation through helping every organizational member feel valued as an important member of the group and appreciated for their unique personal characteristics (fostering a climate for inclusion). Inclusion increases organizational members' emotional attachment to the organization (affective commitment), which then enhances favorable perceptions of innovation wherein members feel comfortable sharing their ideas and perspectives with one another (critical to workplace innovation).